Carcinoma skin in association with Chronic Myeloid Leukemia; a case report (Bangladesh Journal of Medical Science, 2017)
Hydroxyurea (HU) is a cytostatic agent used to treat myeloproliferative disorders including chronic myeloid leukemia (CML), the long term use of which has been seen to be associated with multiple skin disorders. The purpose of this study was to report concomitant occurrence of multiple skin carcinomas in patients on HU & consider an alternative chemotherapeutic agent for myeloproliferative disorders.Bangladesh Journal of Medical Science Vol.16(3) 2017 p.464-466